Experiment on Direction of Arrival Estimation of Atmospheric Spark Discharge Plasma Using Combined Time-Domain Antenna - Jiangzehui Yan; Luping Xu; Weihao Tie; Dan Jiang (International Journal of Antennas and Propagation)
Apart from interfering in the communication system of an aircraft, electromagnetic pulses (EMPs) radiated from spark discharge plasma, which is generated during high-speed flight, can also be utilized in passive detection. In order to validate this idea, an experiment on direction of arrival (DOA) estimation of a spark discharge plasma target using its radiated EMPs is carried out in this paper. A combined time-domain antenna is designed based on the model of spark discharge process and is used to receive the radiated EMPs during the experiment. According to the experimental results, the DOA estimation system with combined antenna is able to obtain the direction information of a spark discharge plasma. Results also show that the estimation performance of elevation angle is better when the actual elevation angle of the discharge plasma target is higher, while the estimation performance of azimuth is opposite. The azimuth angle of a target has very little influence on the DOA estimation. Moreover, the estimation error can be reduced effectively by increasing the aperture size of receiving array. The previously mentioned results provide an approach to locate the discharge plasma source using radiated EMPs with passive detection techniques.